P165 UTILIZATION OF REACTIVE DRUG LEVEL MONITORING IN INFLAMMATORY BOWEL DISEASE. (18th January 2018) - Christophi, George; Walker, Ted; Wade, Gerald; Thomas, Alex; Murphy, Ian; Ciorba, Matthew; Deepak, Parakkal
Abstract: Background: Biologics and thiopurines are standard therapies in the management of Crohn's disease (CD) and ulcerative colitis (UC). Reactive therapeutic drug concentration monitoring (TDM) provides insights into the mechanism of loss of response and allows effective and cost-efficient methods of adjusting dose or switching to a different medication. This study aimed to compare practice patterns of reactive TDM among inflammatory bowel disease (IBD) dedicated gastroenterologists (GIs) in tertiary academic center versus general GIs in the community. Methods: A prospective review of consecutive established and new patient visits at Washington University in Saint Louis between January 1, 2017 and June 30, 2017 was conducted. We examined the utilization of reactive TDM in IBD patients with loss of clinical response and persistent disease activity by clinical, endoscopic, and/or radiological criteria while receiving a biologic medication (anti-TNF or anti-integrin) and/or thiopurine therapy. Statistical analysis was performed using Chi square. Results: The study examined 478 patients with a median age was 44 years, 52% females, 62% with CD, and 14 % African-American. Overall, TDM was utilized for 32% in patients on biologics and 41% on thiopurines. IBD-dedicated compared to general GIs were significantly more likely to utilize reactive TDM in patients taking biologics (40% vs 13%, p=0.01) or thiopurines (46% vs 18 p=0.01). There was a significant inverse association between the incidence of reactive TDM and corticosteroid use (p=0.02). There were no difference in TDM among CD vs UC, age, gender, and race. Conclusion: Reactive TDM is significantly underutilized to manage patients with CD and UC. IBD-dedicated GIs significantly utilize reactive TDM more frequently compared general GIs. Our data highlight the importance of continued education and interventions to improve utilization of reactive TDM to limit corticosteroid exposure and conserve biologic classes in IBD.